Chyawanprash: A review of therapeutic benefits as in authoritative texts and documented clinical literature. (2nd February 2017) - Narayana, D.B. Anantha; Durg, Sharanbasappa; Manohar, P. Ram; Mahapatra, Anita; Aramya, A.R.
Abstract: Ethnopharmacological relevance: Chyawanprash (CP), a traditional immune booster recipe, has a long history of ethnic origin, development, household preparation and usage. There are even mythological stories about the origin of this recipe including its nomenclature. In the last six decades, CP, because of entrepreneurial actions of some research Vaidyas (traditional doctors) has grown to industrial production and marketing in packed forms to a large number of consumers/patients like any food or health care product. Currently, CP has acquired a large accepted user base in India and in a few countries out-side India. Aim of the study: Authoritative texts, recognized by the Drugs and Cosmetics Act of India, describe CP as an immunity enhancer and strength giver meant for improving lung functions in diseases with compromised immunity. This review focuses on published clinical efficacy and safety studies of CP for correlation with health benefits as documented in the authoritative texts, and also briefs on its recipes and processes. Materials and methods: Authoritative texts were searched for recipes, processes, and other technical details of CP. Labels of marketing CP products (Indian) were studied for the health claims. Electronic search for studies of CP on efficacy and safety data were performed in PubMed/MEDLINE and DHARA (Digital Helpline for Ayurveda Research Articles), and Ayurvedic books were also searched for clinical studies. Results: The documented clinical studies from electronic databases and Ayurvedic books evidenced that individuals who consume CP regularly for a definite period of time showed improvement in overall health status and immunity. However, most of the clinical studies in this review are of smaller sample size and short duration. Further, limitation to access and review significant data on traditional products like CP in electronic databases was noted. Conclusions: Randomized controlled trials of high quality with larger sample size and longer follow-up are needed to have significant evidence on the clinical use of CP as immunity booster. Additional studies involving measurement of current biomarkers of immunity pre- and post-consumption of the product as well as benefits accruing with the use of CP as an adjuvant are suggested. Graphical abstract: